Effect of Opuntia elatior on Alteration in Glutamic Oxaloacetic Transaminase activity induced by Gamma Radiation in Swiss Albino Mice: Pharmaceutical Science-Zoology - Kavita Poonia; Jaimala Sharma (International Journal of Life Science and Pharma Research, 2022)
When mice are exposed to gamma radiation, all the body systems are affected adversely. Liver enzymes which are responsible for removal of toxicity created by irradiation increases in the body. Several herbs are known to reduce this toxicity. Opuntia elatior (OE) ,a cactus, was tested in this study for its activity to remove toxins induced by whole body exposure to Co60 gamma rays (6Gy).A moderate dose of OE (10 mg/kg body weight) was given orally to mice, before whole body irradiation and GOT activity was studied in their kidney at 1,3,5,10,15 and 30 post treatment days . Whole body gamma ray exposure increases GOT activity in the kidneys also. In OE pretreated animals this increase was significantly lesser and early recovery was observed. Two types of extracts were used in this study (ethanolic and acetonic). Both were able to reduce gamma radiation induced increase significantly and almost equally. As OE cladode extracts are quite cheap and produce no side effects(OE cladodes are used as food), it may be used to prevent unwanted toxic effects of gamma radiation exposure.